Jämställdhet och mångfald : I Luleå kommun - Andersson, Mia (2014)
Luleå is a growing municipality, which strives for that equality and diversity should be included in all their work. In this thesis the municipality's work with recruitment from a gender diversity perspective was studied. A closer look has been taken at whether and what recruiters are experiencing as difficult about their work on this issue, how they assess the personal qualities and how such work generally tend to look. This has been studied by interviewing five people and, then, based on the interview responses surveys were developed to see if others have the same opinion as the interviewed recruiters. The results show that the majority did not feel that their work with equality and diversity was especially difficult and it was not something that was thought of very much, because it was more seen like something obvious. However there were some difficulties with language, finding the time to view/share materials in the subject matter, and get the underrepresented sex to search the offered positions. There were differences in how they assessed the personal characteristics. They talked about a vague gut instinct, scales, and tables. The result of the surveys then showed that the views of the interviewees were shared among more people working in the municipality of Luleå. The conclusion is that the staff involved in recruitment in Luleå has knowledge of equality and diversity and that they have a lot of help available in the form of material and colleagues. Therefore, the discrimination risk is assessed as low. Validerat; 20141204 (global_studentproject_submitter)